Impact of a mobile decision support tool on antimicrobial stewardship indicators in St. John's, Canada. - Daniel Doyle (Public Library of Science (PLoS), 2021)
Objectives Inappropriate antibiotic use contributes to antimicrobial resistance. The SpectrumTM app provides antibiotic decision support, based on local antimicrobial resistance rates. We determined the impact of regional implementation of the app on inpatient antimicrobial appropriateness, inpatient antimicrobial usage (AMU), population-based Clostridioides difficile infection (CDI) rates and cost, using a retrospective, before and after quasi-experimental design, including a one-year study period. Methods The SpectrumTM app was released to prescribers in February, 2019. We performed two one-day inpatient point prevalence surveys using the National Antimicrobial Prescribing Survey tool, six months before (June 25, 2018) and six months after (June 25, 2019) app dissemination. Inpatient AMU in Defined Daily Dose/1000 patient days and CDI incidence were compared, before and after app dissemination. Results The pre-survey included 184 prescriptions, and the post-survey included 197 prescriptions. Appropriateness was 97/176 (55.1%) pre, and 126/192 (65.6%) post (+10.5%, p = 0.051). Inpatient AMU declined by 6.6 DDD/1000 patient days per month, and CDI declined by 0.3 cases per month. Cost savings associated with reduced AMU were $403.98/bed/year and associated with reduced CDI were $82,078/year. Conclusion We observed improvement in antimicrobial stewardship indicators following SpectrumTM implementation. We cannot determine the cause of these improvements.